2013
DOI: 10.14483/udistrital.jour.calj.2013.1.a01
|View full text |Cite
|
Sign up to set email alerts
|

From Contrastive Rhetoric towards Perceptions of Identity: Written Academic English in Central Mexico

Abstract: De la retórica del contraste a las percepciones de identidad: escritura académica en inglés en México central. AbstractThis research looks at two students at the end of a four year period in academic writing as a second language using open interviews and textual analysis of academic papers. While the initial focus of the research was on the development of rhetorical features in academic texts, issues more oriented to identity construction emerged through the data analysis, implying that long term academic wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…This finding parallels what Crawford et al (2013) found, though those authors reported analyses indicating that participants' L2 did not influence their L1 writing. In the present study, participants were clearly under the influence of L2, as they transferred rhetorical organization and elements from L2 to L1.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This finding parallels what Crawford et al (2013) found, though those authors reported analyses indicating that participants' L2 did not influence their L1 writing. In the present study, participants were clearly under the influence of L2, as they transferred rhetorical organization and elements from L2 to L1.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, after the essays were completed, I conducted semi-structured interviews with the students. I opted for this sort of interviews due to their common applications in the literature as a means of unveiling cognitive processes studied in contrastive rhetoric research (Crawford et al, 2013;Gao, 2012;Hirose, 2003;Kobayashi & Rinnert, 2008;Kubota, 1998;Uysal, 2008).…”
Section: Topics For English and Turkish Opinion Essays English Essay mentioning
confidence: 99%
See 1 more Smart Citation
“…Latin American contexts have probably received less attention in the international sphere (but, for example, Hanauer & Englander, 2011), though national journals increasingly cover such topics. In the case of Colombia, various studies have treated topics related to argumentative and/or academic writing in English as an L+ (Cárdenas, 2003(Cárdenas, , 2014Castañeda, 2012;Chala Bejarano & Chapetón, 2013;Correa, 2010;Crawford, Mora Pablo, Lengelign, & Goodwin, 2013;Escobar Alméciga & Evans, 2014;Gómez, 2011;Janssen, Nausa, & Rico, 2012;Nanwani, 2009;Viáfara Gozález, 2008 (Casanave & Hubbard, 1992;Diab, 2005;Díaz Hormazábal, 2007;Hammann, 2005;Huang, 2010;Jenkins, Jordan, & Weiland, 1993;Leki, 1994;Matsuda, Saenkhum, & Accardi, 2013;Pérez-Llantada et al, 2011;Pittam, Elander, Lusher, Fox, & Payne, 2009;Shi & Cumming, 1995;Wan, 2014;Yildirim & Ilin, 2009). However, most of these have considered the cases of writers already immersed in training programs for academic writing or who at least have become aware of the need for such training due to professional demands.…”
Section: Previous Work On L2 Academic and Rhetorical Writingmentioning
confidence: 99%
“…According to these researchers, the problem arose due to students' lack of understanding in organizing a paragraph in Chinese writing. Other researchers, Crawford et al (2013) have conducted a contrastive rhetoric towards perception of identity which is written in the form of academic English in central Mexico. The result shows that the students have a strong identity with English; however, the writing is more influenced by the Spanish.…”
Section: Introductionmentioning
confidence: 99%